Analysis of Nonlinear Discrete Dynamic Systems in the Cournot Duopoly Model With the Influence of Promotion Costs - Sintauli Atalia Magdalena Silaen; Sri Wigantono; Wasono Wasono (Sora Journal of Mathematics Education, 2025)
In the field of economics, Cournot duopoly is part of an oligopoly market structure consisting of tw firms that have dominant control over a market. Competition between the two firms occurs to determine the optimal quantity of goods to maximize profits. Therefore, an appropriate market strategy is needed to achieve the company’s targets. Based on this issue, mathematical modeling is used to analyze the relationship between the two companies. One important factor in introducing a product is promotional activities. Promotions are carried out as a company strategy to attract consumer attention. Then, if there is an increase in demand for goods from consumers, the company will incur marginal costs. Thus, research is conducted that discusses a discrete Cournot duopoly model in predicting the optimal quantity of goods, with the influence of promotional costs and marginal costs in setting market strategies. The research uses quantitative methods in the form of literature studies and analysis of discrete dynamic systems, which includes determining equilibrium points, local stability analysis of equilibrium points, and numerical simulation of the discrete Cournot duopoly model.